Secularism and Religious Nationalism: A Historical Study of Ethnic Conflict in Myanmar - Ram Hlei Thang (Center for Southeast Asian Social Studies (CESASS), 2019)
Myanmar, also known as Burma, has been plagued by ethnic conflict and civil war for decades since its independence in 1948. Applying historical method, this study examines the relationship between the issue of secularism and ethnic conflict in the country by focusing on the rise of religious nationalisms. This study finds that the rise of Buddhist nationalism among Burmese majority, as well as the rise of Christian nationalism among minority ethnics-have challenged peaceful coexistence and vision of a secular state as aspirated by Burmese founding fathers. This study argues that this failure to adopt the principles of secularism was the root cause of ethnic conflict that has raged the country for over six decades.